Biaxial stress and functional groups (T = O, F, and Cl) tuning the structural, mechanical, and electronic properties of monolayer molybdenum carbide - Komsilp Kotmool; Thanayut Kaewmaraya; Tanveer Hussain; Rajeev Ahuja; Wei Luo; Thiti Bovornratanaraks (Physical Chemistry Chemical Physics, 2022)
preserve their features under the ranges of the strain of -2% to 10% and -1% to 5%, respectively, beyond which they undergo the semiconductor-to-metal transitions. These findings would guide the potential applications in modern 2D straintronic devices.
Keywords: MXene and MAX Phase Materials; 2D Materials and Applications; Graphene research and applications